Synthesis and Electrochemical Characterization of Palladium Crystals Enclosed by (100) Facets by Seed-Mediated Fabrication - Eiji Higuchi; Masashi Kawai; Masanobu Chiku; Hiroshi Inoue (International Journal of Electrochemistry)
Pd crystals enclosed by (100) facets were prepared in an aqueous solution containing cetyltrimethylammonium bromide (CTAB) as the capping agent and ascorbic acid as the reducing agent at 30, 40, and 50°C by a modified seed-mediated fabrication technique. Regardless of the reaction temperature, the absorption peak between 300 and 400 nm assigned to PdCl42- decreased with an increase in the reaction time after the addition of ascorbic acid in the PdCl42- aqueous solution containing CTAB because of Pd deposition. The field emission-scanning electron microscopy images showed that the Pd crystals were enclosed by only (100) facets, and their fractions depended on the reaction temperature. The ratios of the peak current at 0.54 and 0.48 V were 0.60, 0.54, and 0.47 for the samples prepared at 30, 40, and 50°C, respectively, suggesting that the proportion of the (100) facet on the Pd surface was higher at lower temperatures.